2019
DOI: 10.1096/fj.201902172r
|View full text |Cite
|
Sign up to set email alerts
|

The Annexin A1/FPR2 pathway controls the inflammatory response and bacterial dissemination in experimental pneumococcal pneumonia

Abstract: Streptococcus pneumoniae is a major cause of community-acquired pneumonia leading to high mortality rates. Inflammation triggered by pneumococcal infection is necessary for bacterial clearance but must be spatially and temporally regulated to prevent further tissue damage and bacterial dissemination. Annexin A1 (AnxA1) mainly acts through Formyl Peptide Receptor 2 (FPR2) inducing the resolution of inflammation. Here, we have evaluated the role of AnxA1 and FPR2 during pneumococcal pneumonia in mice. For that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 55 publications
(139 reference statements)
5
58
0
Order By: Relevance
“…The following day BMDMs were stimulated with the TLR4 agonist lipopolysaccharide (LPS; from Escherichia coli serotype O:111:B4; 1 μg/ml; Sigma‐Aldrich) for 1 hr as previously described, 23 or stimulated with the TLR2 agonist lipoteichoic acid (LTA; 10 μg/ml; Sigma‐Aldrich) 32 . The AnxA1 peptidomimetic Ac2‐26 (32 μ m; GeneScript) 33 and a selective FPR2 antagonist, WRW4 (10 μ m; Calbiochem) 34 were added into the cells prior to inflammasome activation. Then BMDMs were stimulated with inflammasome activators in RPMI 1640 medium without FBS: MSU crystals (300 μg/ml for 6 hr); 29 Silica (250 μg/ml for 6 hr); 35 adenosine 5′‐triphosphate disodium salt (ATP 5 m m for 30 min); 36 Poly(dA:dT) (Sigma‐Aldrich; 500 ng/ml for 2 hr); 37 Legionella pneumophila bacteria (strain JR32 – MOI of 10 for 4 hr) 37 .…”
Section: Methodsmentioning
confidence: 99%
“…The following day BMDMs were stimulated with the TLR4 agonist lipopolysaccharide (LPS; from Escherichia coli serotype O:111:B4; 1 μg/ml; Sigma‐Aldrich) for 1 hr as previously described, 23 or stimulated with the TLR2 agonist lipoteichoic acid (LTA; 10 μg/ml; Sigma‐Aldrich) 32 . The AnxA1 peptidomimetic Ac2‐26 (32 μ m; GeneScript) 33 and a selective FPR2 antagonist, WRW4 (10 μ m; Calbiochem) 34 were added into the cells prior to inflammasome activation. Then BMDMs were stimulated with inflammasome activators in RPMI 1640 medium without FBS: MSU crystals (300 μg/ml for 6 hr); 29 Silica (250 μg/ml for 6 hr); 35 adenosine 5′‐triphosphate disodium salt (ATP 5 m m for 30 min); 36 Poly(dA:dT) (Sigma‐Aldrich; 500 ng/ml for 2 hr); 37 Legionella pneumophila bacteria (strain JR32 – MOI of 10 for 4 hr) 37 .…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study it has been shown that Ac2-26 reduces the inflammatory response and bacterial loads after pneumococcal pneumonia, and that this protective effect is mediated via FPR2 (43). Interestingly, in that study it was observed that FPR2-deficiency results in higher levels of the pro-inflammatory cytokines compared to WT littermates (43). In our study, we observed higher Tnfα, Ccl3 and Cxcl10 mRNA expression levels in infected Fpr2 −/− compared to WT mice (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Lower neutrophil counts in the CNS of Ac2-26-treated meningitis mice might principally be due to a stimulation of bacterial phagocytosis by Ac2-26 in the periphery (43). To verify or falsify this assumption, we measured in parallel the bacterial load in the peripheral circulation (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the pathogenetic involvement of these molecules qualifies them as relevant drug targets or therapeutics as well. Indeed, accumulating preclinical data have encouraged envisaging DAMPs as therapeutic targets for inhibition [5,[12][13][14][15][16][17] and administration of SAMPs as candidate drugs [5,[18][19][20][21][22][23][24][25][26][27] for treating acute or chronic inflammatory disorders. On the other hand, DAMPs may also be…”
Section: Introductionmentioning
confidence: 99%